Optimasi Proses Injeksi Plastik untuk Mengurangi Cacat Short Mold pada Produk Flip Top Cap - Nadia Febrian; Pani Satwikanitya (Universitas Muhammadiyah Yogyakarta, 2025)
Short mold or short shot defect is one of the major challenges in the plastic injection molding process, occurring due to incomplete material filling in the mold cavity, resulting in improperly formed products. This defect negatively impacts product quality and production efficiency. This study aims to minimize short mold defects in the manufacturing of flip top caps by optimizing barrel temperature and injection pressure parameters. The methodology involves experimental trials using polypropylene material, where variations in barrel temperature and injection pressure were tested to determine the optimal parameter combination. The results indicate that setting the barrel temperature at 245°C with an injection pressure of 55 MPa in zone 1, 220°C with 50 MPa in zone 2, 215°C with 50 MPa in zone 3, and 200°C with 50 MPa in zone 4 produced flip top caps that met standard specifications. These parameters resulted in products with excellent shape stability, optimal cleanliness, consistent color, and weight within industry standards. The optimization of barrel temperature and injection pressure plays a crucial role in enhancing product quality, reducing short mold defects, and improving production efficiency. This study provides valuable insights into determining optimal parameters for the plastic injection process, which can be applied in the manufacturing industry to enhance effectiveness and efficiency in production.